Virulence-related genotypic differences among Bacillus cereus ocular and gastrointestinal isolates and the relationship to endophthalmitis pathogenesis - Coburn, Phillip S.; Miller, Frederick C.; LaGrow, Austin L.; Mursalin, Huzzatul; Gregory, Anna; Parrott, Aaron; Astley, Daniel; Callegan, Michelle C. (Frontiers in Cellular and Infection Microbiology, 2023)
Background Bacillus cereus (Bc) can cause self-limiting gastrointestinal infections, but when infecting the eye, can cause rapid and irreversible blindness. This study investigated whether clinical ocular and gastrointestinal Bc isolates differed in terms of virulence-related genotypes and endophthalmitis virulence. Methods Twenty-eight Bc ocular, gastrointestinal, and laboratory reference isolates were evaluated. Hemolysis assays were performed to assess potential differences in hemolytic activity. The presence of twenty Bc virulence-related genes was assessed by PCR. A subset of ocular and gastrointestinal isolates differing in PCR positivity for 5 virulence genes was compared to strain ATCC14579 in an experimental murine model of endophthalmitis. At 8 hours post infection, retinal function was evaluated by electroretinography, and intraocular bacterial concentrations were determined by plate counts. Results Gastrointestinal Bc isolates were more hemolytic than the Bc ocular isolates and ATCC14579 (p < 0.0001). Bc ocular isolates were more frequently PCR-positive for capK, cytK, hblA, hblC, and plcR compared to the gastrointestinal isolates (p ≤ 0.0002). In the endophthalmitis model, mean A-wave retention did not differ significantly between eyes infected with ATCC14579 and eyes infected with the selected ocular or gastrointestinal isolates (p ≥ 0.3528). Similar results were observed for mean B-wave retention (p ≥ 0.0640). Only one diarrheal isolate showed significantly greater B-wave retention when compared to ATCC14579 (p = 0.0303). No significant differences in mean A-wave (p ≥ 0.1535) or B-wave (p ≥ 0.0727) retention between the selected ocular and gastrointestinal isolates were observed. Intraocular concentrations of ATCC14579 were significantly higher than the selected ocular isolate and 3 of the gastrointestinal isolates (p ≤ 0.0303). Intraocular concentrations of the selected ocular isolate were not significantly different from the gastrointestinal isolates (p ≥ 0.1923). Conclusions Among the subset of virulence-related genes assessed, 5 were significantly enriched among the ocular isolates compared to gastrointestinal isolates. While hemolytic activity was higher among gastrointestinal isolates, retinal function retention and intraocular growth was not significantly different between the selected ocular and gastrointestinal isolates. These results suggest that Bc strains causing gastrointestinal infections, while differing from ocular isolates in hemolytic activity and virulence-related gene profile, are similarly virulent in endophthalmitis.